1984
DOI: 10.2307/280019
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Aboriginal Tobaccos in Eastern North America

Abstract: SEM micrographs of seeds from four tobaccos historically cultivated by aboriginal groups in the Eastern Woodlands and adjacent Great Plains of North America are presented. The tobaccos considered are Nicotiana rustica L., N. attenuata Torr., N. bigelovii var. quadrivalvis (Pursh) East, and N. bigelovii var. multivalvis (Lindley) East. Micrographs of seeds from herbarium collections are compared with micrographs of carbonized tobacco seeds from the Extended Middle Missouri component at the Travis I site, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Previously documented early dates for the rest of North America have generally fallen between A.D. 400 and 800 [3,13,26,27]. Recently derived dates from the Southwest are significantly earlier.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previously documented early dates for the rest of North America have generally fallen between A.D. 400 and 800 [3,13,26,27]. Recently derived dates from the Southwest are significantly earlier.…”
Section: Discussionmentioning
confidence: 94%
“…The earliest archaeobotanical evidence of the use of tobacco in eastern North America comes from the central Mississippi Valley between A.D. 100 and 200 (uncalibrated) [1,2,13,27,29]. Previously documented early dates for the rest of North America have generally fallen between A.D. 400 and 800 [3,13,26,27].…”
Section: Discussionmentioning
confidence: 98%
“…This is significant as the current state of ethnobotanical data for tobacco dates to the first century A.D., centuries after the dates of the smoking pipes analyzed in this research program so far. The earliest archaeobotanical evidence of the use of tobacco in eastern North America comes from the central Mississippi Valley between A.D. 100 and 200 (uncalibrated) (Asch, 1991;Asch, 1994;Haberman, 1984;Wagner, 2000;Winter, 2000a), with dates for the rest of Eastern North America falling several centuries later (Haberman, 1984;Von Gernet, 1992). Recently derived dates from the Southwest are earlier, with specimens from New Mexico dated to 1040 B.C.…”
Section: Discussionmentioning
confidence: 98%
“…While some have suggested that tobacco use was late, appearing in southeast North America only around 1000 CE, and as late as the historic period in the American southwest (Ford, 1981), more recent work suggests a much greater antiquity. Data from eastern and southwestern North America suggests use of tobacco by 2000-3000 years ago, though the particular species of tobacco is not known (Adams, 1990;Haberman, 1984;Pauketat et al, 2002;Rafferty, 2002Rafferty, , 2006Rafferty et al, 2012;Winter, 2000a). As well, there seems to be consensus that Nicotiana rustica reached the Eastern USA and Canada from South America by 3000 and 2000 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Because nicotine is relatively stable and can survive over archaeological time scales (Rafferty, 2002(Rafferty, , 2006Rafferty et al, 2012;Tushingham et al, 2013), and is typically introduced to the body via the mouth, we hypothesized that it may preserve in dental calculus. Tracing the ancient spread of tobacco in the Americas has traditionally relied on the presence of pipes and/or charred tobacco seeds (e.g., Adair, 2000;Adams and Toll, 2000;Carrasco et al, 2015;Echeverría et al, 2014;Gili et al, 2017;Haberman, 1984;Pauketat et al, 2002;Wagner, 2000;papers in Bollwerk andTushingham, 2016, Rafferty andMann, 2004), and more rarely preserved leaves, and/or quids (e.g., Adams et al, 2015;Fewkes, 1912:143;Jones, 1935;Morris, 1960) andpollen (e.g., Cummings, 2000). However, these items are rare in the archaeological record and are not linked to particular individuals, unless associated with specific burials, and even then, association with an individual is an inference rather than a direct measurement.…”
Section: Introductionmentioning
confidence: 99%